Phenolics compounds and antioxidant activities from optimized Phoenix dactylifera extract using response surface methodology - Abd Gani, Siti Salwa; Ramli, Nur Asyiqin; Halmi, Mohd Izuan Effendi; Mat Radzi, Salina (Malaysian Institute of Chemistry, 2024)
Phoenix dactylifera has been documented to possess numerous health potentials as it contains a myriad of bioactive compounds. P. dactylifera was extracted in this study, and extraction conditions through Soxhlet extraction procedures were improved by adopting response surface methodology (RSM). The effects of extraction time (3 h, 4.5 h, and 6 h), solute-to-solvent ratio (1:10, 1:20, and 1:30 g/mL), and size of sample (1.00 mm, 2.87 mm, and 4.75 mm) on total phenolic content (TPC), total flavonoid content (TFC) and 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) radical scavenging activity were determined. The present study demonstrated the quadratic polynomial coefficients had a significant impact (p < 0.05) for all models, with a non-significant lack of fit at p > 0.05 and R2 exceeded 0.90 respectively. The best extraction conditions obtained were as follows: time for extraction (6 h), solute-to-solvent ratio (1:10), and size of sample (4.75 mm). Under ideal conditions, the TPC, TFC, and DPPH radical scavenging activity were 50.25 mg GAE/g, 11.14 mg QE/g, and 79.22% respectively. The phenolic compounds in the extract were screened and recorded by using Ultra High-Performance Liquid Chromatography-Quadrupole Time of Flight-Mass Spectrometry (UHPLC-QTOF-MS). Eleven phenolic compounds of prime importance in P. dactylifera extract were identified. This work indicated that P. dactylifera has a unique phytochemical profile which has antioxidant potential to be an adjunct in preventing a variety of diseases.